Heart rate variability indices, biomarkers and cardiac nerve density: Independent surrogate markers for diagnosis of diabetic cardiac autonomic neuropathy in type 2 diabetes mellitus animal model - Akinlade, Olawale Mathias; Owoyele, Bamidele Victor; Soladoye, Olufemi Ayodele (International Journal of Health Sciences, 2020)
Objectives: Heart rate variability (HRV) has been shown to represents a promising quantitative marker of autonomic activity. Studies have shown that diabetic patients and animal models have derangements in certain biochemical parameters with reduced cardiac nerve density following development of diabetic cardiac autonomic neuropathy (DCAN). This study, therefore, aims to correlate HRV indices, cardiac histology, and cardiac nerve density with selected biochemical markers in the DCAN rat model using high fat diet (HFD) and streptozotocin (STZ) induction. Methods: DCAN was induced in Wistar rats using HFD for 8 weeks with 25 mg/kg STZ daily for 5 days. DCAN features were then assessed using Holter electrocardiography (ECG), invasive biomarkers, and cardiac histology. Results: DCAN group had significantly higher advanced glycated end product levels (P < 0.0001), noradrenaline (P = 0.010), and insulin resistance (P = 0.016) compared with controls. The level of antioxidants, sorbitol dehydrogenase activity (P = 0.009), nerve growth factors (P < 0.0001), and choline acetyl-transferase (P = 0.031) was, however, significantly reduced. Furthermore, HRV indices which were also reduced with DCAN induction correlated significantly with levels of biomarkers and cardiac nerve density. Conclusion: HRV is a cheap and easy tool for assessing DCAN that significantly correlates with markers of autonomic activity. Holter ECG and HRV evaluation should be considered early in patients with diabetes.